Metformin-Loaded Polymer-Based Microbubbles/Nanoparticles Generated for the Treatment of Type 2 Diabetes Mellitus - ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN (American Chemical Society, 2021)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease that is increasingly common all over the world with a high risk of progressive hyperglycemia and high microvascular and macrovascular complications. The currently used drugs in the treatment of T2DM have insufficient glucose control and can carry detrimental side effects. Several drug delivery systems have been investigated to decrease the side effects and frequency of dosage, and also to increase the effect of oral antidiabetic drugs. In recent years, the use of microbubbles in biomedical applications has greatly increased, and research into microactive carrier bubbles continues to generate more and more clinical interest. In this study, various monodisperse polymer nanoparticles at different concentrations were produced by bursting microbubbles generated using a T-junction microfluidic device. Morphological analysis by scanning electron microscopy, molecular interactions between the components by FTIR, drug release by UV spectroscopy, and physical analysis such as surface tension and viscosity measurement were carried out for the particles generated and solutions used. The microbubbles and nanoparticles had a smooth outer surface. When the microbubbles/nanoparticles were compared, it was observed that they were optimized with 0.3 wt % poly(vinyl alcohol) (PVA) solution, 40 kPa pressure, and a 110 μL/min flow rate, thus the diameters of the bubbles and particles were 100 ± 10 μm and 70 ± 5 nm, respectively. Metformin was successfully loaded into the nanoparticles in these optimized concentrations and characteristics, and no drug crystals and clusters were seen on the surface. Metformin was released in a controlled manner at pH 1.2 for 60 min and at pH 7.4 for 240 min. The process and structures generated offer great potential for the treatment of T2DM. ©